Planning and urban change - Ward, Stephen V. (Stephen Victor) (Sage Publications, 2004)
An accessible yet detailed account of British urban planning. This second edition features an entirely new chapter on the key policy changes that have occurred under the Major and Blair governments, together with a critical review of current policy trends.